Penciptaan Dress Lilit Motif Bunga Easter Lily Dengan Teknik Batik Tulis - Mikha Exclesia Pasaribu; Sri Wiratma; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This creation is based on Batik as a rich Indonesian cultural heritage, which continues to undergo significant transformation by combining traditional elements and modern fashion trends. The creation of a new batik motif inspired by the Easter lily flower, was chosen because of its symbolic meaning and natural beauty. The design of this motif consists of three elements: the main motif of the Easter lily flower, supporting motifs, and isen motifs as complementary details. This creation aims to determine the process and results of applying Easter lily motif batik cloth to a wrap Dress using the batik tulis technique. This creation uses the Alma M. Hawkins method which has 5 stages of creation, namely: preparation, elaboration, synthesis, concept realization, and completion. The result of this creation is the creation of a wrap Dress with an Easter lily flower motif of 12 batik works. This batik tulis uses the colet technique with remasol dye. The wrap batik Dress with the Easter lily motif is expected to foster the interest of the younger generation in wearing batik tulis with colors and motifs that are tailored to their tastes.